Percutaneous cavitary lavage in the diagnosis of pulmonary cavities - Belet, Umit; Fındık, Serhat; Ozmen, Zafer; Atici, Atilla Guven; Akan, Huseyin (Journal of Thoracic Disease, 2013)
Objective: To investigate diagnostic significance of percutaneous cavitary lavage (PCL) in differential diagnosis of benign and malignant pulmonary cavitary lesions. Methods: An alternative diagnostic method called PCL was performed on 16 patients having peripherally located pulmonary cavitary lesions with thin walls which were not suitable for tissue biopsy and whose diagnosis could not be made by sputum examination and bronchoscopic procedures. A 22-gauge needle was inserted into the cavity under computed tomography (CT) guidance. Saline was injected through the needle and then aspirated. The specimen was examined cytologically and microbiologically. Results: PCL could make a correct diagnosis in 12 of 16 patients (75%). In three patients (18.7%) appropriate specimen could not be taken. Diagnostic sensitivity and specificity of PCL for malignant-benign differentiation was 80% and 100%, respectively. The accuracy of PCL for this differentiation was 92.3%. There was only one complication, a small pneumothorax resolved without any intervention. Conclusions: PCL is an alternative method in the differential diagnosis of thin walled pulmonary cavitary lesions especially for patients whose diagnosis could not be made by sputum and bronchoscopic procedures and who are not suitable for cutting needle biopsy.